2022
DOI: 10.3389/fimmu.2022.924244
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically upregulated mast cell CPA3 patterns in chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis

Abstract: BackgroundThe mast cell-specific metalloprotease CPA3 has been given important roles in lung tissue homeostasis and disease pathogenesis. However, the dynamics and spatial distribution of mast cell CPA3 expression in lung diseases remain unknown.MethodsUsing a histology-based approach for quantitative spatial decoding of mRNA and protein single cell, this study investigates the dynamics of CPA3 expression across mast cells residing in lungs from control subjects and patients with severe chronic obstructive pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…The tissue used was macroscopically healthy distal to the tumour, nevertheless it is of course possible that the disease has affected the included mast cells. In this context it is worth noting that CPA3 counts were high ( Figure 3 ) and CPA3 expression has been shown to correlate to decreased lung function in patients with severe chronic obstructive pulmonary disease (COPD) and idiopathic lung fibrosis (IPF) ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue used was macroscopically healthy distal to the tumour, nevertheless it is of course possible that the disease has affected the included mast cells. In this context it is worth noting that CPA3 counts were high ( Figure 3 ) and CPA3 expression has been shown to correlate to decreased lung function in patients with severe chronic obstructive pulmonary disease (COPD) and idiopathic lung fibrosis (IPF) ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical incidence of COPD is high, and its main features include expiratory airflow limitation that is not fully reversible, deregulated chronic airway inflammation, and emphysematous destruction of the lungs [2]. It might affect many other organs and cause other diseases include pneumonia [3], respiratory viral infections [4], pneumothorax [5], heart problems [6], osteoporosis [7], depression and anxiety [8], lung cancer [9], pulmonary hypertension [10], secondary polycythemia [11], idiopathic pulmonary fibrosis [12], obesity [13] and diabetes mellitus [14]. Airway inflammation is triggered by both genetic susceptibility [15] and environmental factors [16].…”
Section: Introductionmentioning
confidence: 99%
“…Other asthma and COPD studies have also reported that lung tissue mast cell gene expression and mast cell counts are dissociated 2 19. Increased CPA3 gene expression was demonstrated in areas of increased collagen deposition in COPD, suggesting a role for CPA3 in tissue remodelling 15. Alternatively, CPA3 may be protective by suppressing levels of vasoconstrictor and bronchoconstrictor molecules 20.…”
mentioning
confidence: 97%
“…The pathophysiological role of mast cells in COPD is unclear, with studies reporting increased, similar or reduced numbers of pulmonary mast cells in COPD vs controls 13–15. There are various published mast cell signatures that can be used to understand mast cell activation, such as an 11-gene mast cell signature derived from single-cell RNA sequencing of lung tissue which includes CPA3 and was upregulated in asthma bronchial biopsies 16.…”
mentioning
confidence: 99%
See 1 more Smart Citation